Evaluation of Life Cycle Costs for Agarwood Oil Extraction with Microwave and Ultrasonic-Assisted Techniques - Saputra, Hendra; Satria, Benni; Nazir, Novizar; Anggraini, Tuty; Salim, Emil (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
Agarwood oil extraction is a crucial process in the agarwood industry. However, this extraction is seldom performed by communities due to its lack of profitability and the extensive duration of the process. This study aims to investigate innovative techniques such as ultrasonic and microwave-assisted maceration to enhance the yield of agarwood oil extraction. Additionally, it seeks to calculate the efficiency of time and cost by determining the life cycle cost of agarwood oil extraction. The methodology employed in this study involved conducting extractions using ultrasonic-assisted maceration, microwave-assisted maceration, and a combination of ultrasonic and microwave-assisted maceration. The results indicated that the extraction method yielding the highest output utilized a combination of microwave-assisted maceration for 3 minutes and ultrasonic-assisted maceration for 60 minutes, producing a yield of 0.15%. When extrapolated to 24 hours, this method would yield 18 grams of agarwood oil extract with an additional cost of Rp13,037. In contrast, the solvent maceration process using microwaves yielded 0.096% of agarwood oil at a lower cost of Rp3,190, producing 12 grams of extract over a 24-hour extraction period. the compounds that make up the composition of agarwood oil are 2-((2S,4aR)-4a,8-Dimethyl-1,2,3,4,4a,5,6,7-octahydro-naphthalen (11.38%), Hydrocinnamic acid (11.13%), Hydrocinnamic acid (11.13%) and (3R,3aR,4aS,5R,9aS)-3,5,8-Trimethyl-3a,4,4a,5,6,7,9,9a-octahydro (10.90%).